Application of Technology in Islamic Economic Development to Maximize Opportunities and Overcome Challenges in the Era of Globalization - Darsimon, Darsimon; Syahril, La Ode Muhamad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The Islamic banking sector in particular has shown very rapid growth, with Islamic banks offering products such as mudharabah (profit sharing), musharakah (capital cooperation), murabahah (buying and selling on margin), and ijarah. The application of fintech and digitalization in the Islamic economy allows for wider access to financial services, including for previously underserved individuals and small businesses. Technology has become a key driver of innovation in various sectors of the economy. The integration of technology in Islamic economics can provide new opportunities for development and efficiency, but it also faces unique challenges that need to be identified and addressed. Problems that often exist in the application of technology have not been able to support the development of the sharia economy. In addition, the opportunities that can be used for the efficiency and inclusion of the sharia economy through technology have not been explored in depth and also no less important is the issue of sharia regulations that can be adjusted to facilitate the integration of technology in the sharia economy. The type of research used is a qualitative research method, with the aim of exploring the views and experiences of practitioners, experts, and stakeholders regarding the application of technology in the sharia economy. The data collection technique uses in-depth interviews, focus group discussions, and case studies. Innovations in the form of sharia mobile banking applications offer features such as account opening, fund transfers, and reporting in accordance with sharia principles. It expands access to financial services, especially in underserved areas. There are significant differences in technology adoption rates between urban and rural areas, as well as between developed and developing countries. This can hinder the spread of technological benefits in Islamic economics equally. The gap in technology access between more developed and less developed regions requires special attention. Mobile banking technology and financial applications facilitate access to Islamic financial services, especially in underserved areas.